The Effectiveness of Trauma Prevention Programs in At-Risk Middle Eastern Communities - Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution; Nurzahara Sihombing (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
This meta-analytic study systematically examines the effectiveness of trauma prevention interventions implemented in at-risk communities across the Middle East by analyzing 47 independent studies (N = 12,483) published between 2010 and 2023. Employing a random-effects model, the findings reveal that these prevention programs have a significantly positive impact on reducing trauma symptoms (g = 0.73, 95% CI [0.65, 0.81], p < .001). Moreover, programs implemented within school environments demonstrated the highest level of effectiveness (g = 0.86), followed by community-based interventions (g = 0.71), and programs involving families (g = 0.62). Further moderator analysis indicates that the duration of program implementation (β = 0.31, p < .01) and the degree of family involvement (β = 0.28, p < .01) are significant predictors of intervention success. Meanwhile, the average rate of incomplete participation (drop-out) was recorded at 18.4 percent, with substantial variation across implementation contexts (SD = 12.3 percent). Meta-regression demonstrated a significant correlation between the level of social support received by participants and the reduction in trauma symptoms experienced (R² = 0.42, p < .001). These findings significantly exceed earlier reports such as those by Peltonen and Punamäki (2010) and Marwat et al. (2025), who estimated program effects within a moderate range (g = 0.45–0.52). Beyond confirming the effectiveness of these interventions, this study highlights the crucial role of local community support and the integration of cultural values as key components in optimizing program outcomes. Accordingly, the findings broaden both the theoretical and empirical horizons of understanding regarding the dynamics of successful trauma prevention programs in Middle Eastern conflict zones, particularly through the identification of mediating mechanisms such as community resilience and the influence of socio-cultural factors as primary moderators in the effectiveness of psychosocial interventions.